Combination treatment of dupilumab with bortezomib in a patient with IgG kappa gammopathy of renal significance, uremic pruritus and chronic lichenoid dermatitis - Giovanni, Paolino; Di Nicola, Matteo Riccardo; Marcatti, Magda; Bianchi, Vittoria; Ferla, Valeria; Mercuri, Santo Raffaele (Acta Biomedica Atenei Parmensis, 2023)
Chronic pruritus (CP) is one of the most frequent symptoms among dermatological conditions, capable of reducing the quality of life (QoL). CP may be induced by atopic dermatitis or other dermatological and/or non-dermatological conditions. In this article, we report the case of a patient affected by generalized CP, characterised by multiple papulo-nodular and escoriatic lesions, developed after the onset of an immunoglobulin G (IgG) kappa monoclonal gammopathy of renal significance (MGRS), associated with renal insufficiency. Therefore, a combined treatment with dupilumab for CP and bortezomib for the hematologic malignancy was administered to the patient. The present case report highlights the efficacy of dupilumab for the treatment of CP. Moreover, no relevant side effects were recorded during the treatment in combination with other systemic biological drugs for other systemic pathologies.